Structural performance evaluation of an excavator under variations of static loading using the finite element method - Reson Wibowo; Nurjaya; Zaenal Aripin (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
The excavator bucket is a primary working component is a primary working component of heavy equipment that is subjected to repetitive static and dynamic loading during operation. Therefore, an adequate structural performance evaluation is required to ensure safety and operational reliability. This study evaluates the stress distribution, displacement, and safety factor of an excavator bucket structure using the Finite Element Method (FEM). A three-dimensional bucket model was developed using FEM-based numerical simulation software, with ASTM A36 structural steel assumed as the material. Static load variations of 196 N, 392 N, and 588 N (converted from 20 kg, 40 kg, and 60 kg using gravitational acceleration of 9.81 m/s²) were applied uniformly to the bucket, while fixed boundary conditions were imposed at the bucket–arm connection. The simulation results show that increasing load levels lead to a significant increase in Von Mises stress and maximum displacement, accompanied by a reduction in the safety factor. The results indicate that under load levels of 392 N and 588 N, the maximum Von Mises stress exceeds the yield strength of ASTM A36 steel (248.23 MPa), indicating plastic deformation and structurally unsafe conditions, the highest load condition indicates that the structure approaches a critical operating state. The results of this study provide a technical basis for evaluating and improving excavator bucket structural design to enhance safety and durability.